2018
DOI: 10.1186/s12967-018-1684-3
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency in interleukin-18 promotes differentiation of brown adipose tissue resulting in fat accumulation despite dyslipidemia

Abstract: BackgroundThe cytokine, interleukin-18 (IL-18), was originally identified as an interferon-γ-inducing proinflammatory factor; however, there is increasing evidence suggesting that it has non-immunological effects on physiological functions. We have previously investigated the potential pathophysiological relationship between IL-18 and dyslipidemia, non-alcoholic fatty liver disease and non-alcoholic steatohepatitis, which were mediated by lipid energy imbalance. Therefore, herein we focused on brown adipocytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 57 publications
4
15
0
1
Order By: Relevance
“…In our previous study, it was hypothesized that IL-18 may serve as a novel option for treatment of metabolic disorders, such as diabetes mellitus and dyslipidemia, and for neuropsychiatric disorders, such as MDD (9,11,12). The results of the present study support the notion that IL-18 may serve as a novel treatment strategy of metabolic and neuropsychiatric disorders, including MDD.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…In our previous study, it was hypothesized that IL-18 may serve as a novel option for treatment of metabolic disorders, such as diabetes mellitus and dyslipidemia, and for neuropsychiatric disorders, such as MDD (9,11,12). The results of the present study support the notion that IL-18 may serve as a novel treatment strategy of metabolic and neuropsychiatric disorders, including MDD.…”
Section: Discussionsupporting
confidence: 84%
“…An inactive 24-kDa precursor form of IL-18 is cleaved by activated caspase-1 to a mature 18-kDa active form (4)(5)(6)(7). In addition to its role as an inflammatory cytokine, IL-18 also serves a role in energy metabolism, and in the central nervous system it is involved in psychiatric disorders such as depression (8)(9)(10)(11)(12). Regarding energy homeostasis, IL-18 deficiency induces bulimia, corpulency and insulin resistance which resembles type 2 diabetes mellitus (8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, C57BL7 mice deficient for IL-18 are extremely sensitive to obesity but also exhibit larger brown adipocytes and a higher UCP-1 expression in BAT compared to wild-type littermates [240]. To support the role of IL-18 in this process, exogenous administration of IL-18 in these mice restores the adipocyte size as well as the expression of UCP-1 [240]. The precise action of IL-18 is likely to be complex and possibly independent from the IL-18 receptor (IL-18r).…”
Section: Cellular Responses To Mitochondrial Uncouplingmentioning
confidence: 99%
“…It is worth noting that the IL-18 and IL-1β released by MAFLD during pyroptosis seem to be a double-edged sword [ 113 ]. Studies by Yamanishi et al have demonstrated that IL-18 is essential for normal lipid metabolism in the liver and that its deficiency causes fat accumulation [ 120 ]. However, IL-1β is considered a pro-inflammatory cytokine that promotes the development of MAFLD.…”
Section: Pyroptosis and Mafldmentioning
confidence: 99%